Analysis of Stunting Factors in Children Aged 24-59 Months during The Covid-19 Pandemic - Ezalina, Ezalina; Hasana, Ulfa; Malfasari, Eka (Fakultas Ilmu-ilmu Kesehatan, 2022)
The COVID-19 pandemic has caused many parents to lose their jobs and impacted their ability to purchase healthy food, affecting their children's development. This study aims to determine the factors that influence stunting in children during the COVID-19 pandemic. This was a cross-sectional study. The population was mothers who had toddlers aged 24-59 months (n=145). The sample was chosen through simple random sampling. The data were collected through height tests, interviews, and questionnaires. A univariate analysis was used to obtain a picture of each variable. The bivariate analysis was conducted with the chi-square test, and the multivariate analysis was performed using binary logistic regression. The results showed that 25.5% of children were experiencing stunting. There was a significant relationship between the eating habits of toddlers, childcare, history of infectious disease, mothers’ visitation to health services, mothers’ education level, and family income level with the prevalence of stunting. The level of family income has the most dominant relationship with stunting prevalence. Therefore, during the COVID-19 pandemic, it is essential to lower the prevalence of stunting through cross-sectoral collaborations regarding health service modifications according to the socio-economic level of the community and the incidence of COVID-19 cases.